The use of the Khoury technique for vertical augmentation of atrophic alveolar ridges: A systematic review (Research, Society and Development, 2024)
One of the most important factors to be considered in rehabilitation with implants is the quantity and quality of bone available to perform the surgery, primary stability of the implant and its long-term maintenance. Different techniques for increasing bone thickness and height have been developed, determining which technique to use depends directly on some factors, including the extent and location of the bone defect. One of the techniques that has been widely discussed is the Khoury technique or Split Bone Block (SBB) technique, which proposes the fixation of thinner autogenous bone blocks, in the form of bone sheets, associated with filling with particulate bone and tunneled access. Many studies have demonstrated good results related to this type of technique, presenting satisfactory gains in bone height, favorable for success of the treatment. Thus, the objective of the present study was to review the concepts regarding vertical bone reconstructions and bring the main aspects and results related to the Khoury technique. The aim is to provide a better scientific basis for the implant dentist when selecting this technique. To this end, a systematic review was carried out where the results showed that the Khoury technique presents itself as an excellent alternative for vertical bone gains, being indicated for vertical gains prior to dental implant surgery.